[6]-gingerol and [6]-shogaol, active ingredients of the traditional Japanese medicine hangeshashinto, relief oral ulcerative mucositis-induced pain via action on Na+ channels. (March 2017) - Hitomi, Suzuro; Ono, Kentaro; Terawaki, Kiyoshi; Matsumoto, Chinami; Mizuno, Keita; Yamaguchi, Kiichiro; Imai, Ryota; Omiya, Yuji; Hattori, Tomohisa; Kase, Yoshio; Inenaga, Kiyotoshi
Graphical abstract: Abstract: The traditional Japanese herbal medicine hangeshashinto (HST) has beneficial effects for the treatment of oral ulcerative mucositis (OUM) in cancer patients. However, the ingredient-based mechanism that underlies its pain-relieving activity remains unknown. In the present study, to clarify the analgesic mechanism of HST on OUM-induced pain, we investigated putative HST ingredients showing antagonistic effects on Na + channels in vitro and in vivo. A screen of 21 major ingredients using automated patch-clamp recordings in channel-expressing cells showed that [6]-gingerol and [6]-shogaol, two components of a Processed Ginger extract, considerably inhibited voltage-activated Na + currents. These two ingredients inhibited the stimulant-induced release of substance P and action potential generation in cultured rat sensory neurons. A submucosal injection of a mixture of [6]-gingerol and [6]-shogaol increased the mechanical withdrawal threshold in healthy rats. In a rat OUM model, OUM-induced mechanical pain was alleviated 30 min after the swab application of HST despite the absence of anti-bacterial and anti-inflammatory actions in the OUM area. A swab application of a mixture of [6]-gingerol and [6]-shogaol induced sufficient analgesia of OUM-induced mechanical or spontaneous pain when co-applied with a Ginseng extract containing abundant saponin. The Ginseng extract demonstrated an acceleration of substance permeability into the oral ulcer tissue without an analgesic effect. These findings suggest that Na + channel blockage by gingerol/shogaol plays an essential role in HST-associated analgesia of OUM-induced pain. This pharmacological mechanism provides scientific evidence supporting the use of this herbal medicine in patients suffering from OUM-induced pain.